Primate dentition : an introduction to the teeth of non human primates - Swindler, Daris Ray (Cambridge studies in biological and evolutionary anthropology, 2002)
Primate Dentition is a comprehensive reference work on the teeth of extant primates that will serve as a benchmark for researchers in primatology, physical anthropology, comparative anatomy and vertebrate paleontology.